BERPIKIR KRITIS DAN BERPIKIR KREATIF PEKERJA PEREMPUAN DI SURABAYA UNTUK KESEJAHTERAAN KELUARGA MELALUI PENINGKATAN KUALITAS HIDUP KELUARGA - Rina Dewi; Wiratna Wiratna (STIE Mahardhika, 2020)
The purpose of this study is to look at the effect of critical thinking and creative thinking on family welfare through intervening variables of quality of life in women workers in Surabaya. The concept of a research framework is built on understanding existing theories about critical thinking, creative thinking and reconstruction of family welfare through the quality of family life. This study consisted of 305 samples of female workers in Surabaya who had school-age children. Data obtained from questionnaires distributed to respondents. Using Structural Equation Modeling statistical modeling techniques, with Stata 14 Software. Critical thinking and creative thinking are needed for women workers to be able to do time, mind and energy management for office work and household chores so that a better quality of life will ultimately lead to family welfare. From this study the results were obtained the first model Y = 0.51 X1 + 0.47 X2, which means that exogenous variables consisting of critical thinking (X1) and creative thinking have a positive and significant effect on intervening endogenous variables, namely quality of life (Y) The Second Model Z = 0.93 Y which means the quality of life variable (Y) has a positive and significant effect on the dependent variable namely family welfare (Z). All latent variable indicators have a positive and significant effect with z values> 1.96. This research illustrates the importance of critical thinking and creative thinking for women workers in fighting for the quality of family life in order to achieve a prosperous family. This cannot be formed quickly, it takes time to continue to enrich themselves with new knowledge and insights.